P0075EXPERT OPINION ON THE MULTIDISCIPLINARY MANAGEMENT OF CYSTINOSIS IN ADOLESCENT AND ADULT PATIENTS. (6th June 2020) - Webb, Nicholas; Das, Anibh M; Hulton, Sally; Levtchenko, Elena; Servais, Aude; Wanner, Christoph
Abstract: Background and Aims: Cystinosis is a rare autosomal recessive lysosomal storage disorder caused by mutations in the CTNS gene on chromosome 17p13. It affects between 1:150, 000–1:200, 000 live births, with a prevalence of approximately 1.6 per million. It is a life-long progressive disease which results in an abnormal lysosomal accumulation of the amino acid cystine in multiple organs and tissues of the body. The most common presentation of cystinosis (95%) is the infantile nephropathic form, with renal symptoms developing in the first few months of life. Over the next 10–20 years, extra-renal manifestations of cystinosis become apparent, which require multidisciplinary care. Here we describe a consensus-based programme with the objective of creating clinical recommendations to support HCPs with the management of adolescents and adults living with the multi-organ effects of cystinosis. Method: The programme was led by a Steering Committee (SC) of European clinicians with expertise in managing cystinosis. Recommendations were developed using a quasi-Delphi methodology. The SC identified and prioritised a list of key questions. An Extended Faculty (EF) of additional specialists with extensive experience managing cystinosis in patients of all ages, were invited to answer the questions via an online digital platform. The consolidated answers of expert opinion were summarised into recommendations that were supported by evidence-based guidance and additional published data where possible. The EF were invited to agree / disagree with the draft clinical recommendations. Where there was disagreement, the SC members amended the recommendations and the EF re-voted on the revisions. This process continued until consensus was achieved on all final recommendations. Results: The expert-agreed clinical recommendations reflect the multi-organ effects of cystinosis. Thus, advice on factors relating to the nervous system, muscle involvement, ophthalmology, cardio-respiratory system, dental care and nutrition, dermatology, endocrine system, and gastrointestinal and hepatological involvement, are given, along with renal considerations. Guidance on fertility and family planning that reflect some of the major advances in recent years, are also provided. Ideas on improving psychological well-being and adherence includes recommendations on the use of validated screening tests, increasing access to occupational therapy, and interacting with patient groups. The programme has also produced an online checklist to support HCPs in their daily clinical practice by providing a focus to guide regular consultations with the patient. Conclusion: These expert recommendations offer HCPs relevant advice that support them in the management of adolescents and adults living with the multi-organ effects of cystinosis. The recommendations complement existing international and local guidance and aim to improve patient outcomes.